Development of 3D boiler header template using Webots - Basri N.M.H.; Sahari K.S.M.; Mohideen S.S.K.; Roslin N.S.; Anuar A. (Elsevier Ltd, 2023)
Offline boiler header inspection is a tedious process if done manually since the opening is very small to insert big instruments and tools while the length can range up to 20 m. The geometry can also be complex since boiler tubes are connected to these headers from different directions. Designing of robots to assist in offline boiler header inspections can be made easier if a simulator is available for deciding the parameters of the robot. This paper describes the development of a 3D boiler header pipe environment template for boiler header inspection robot (BHIR) using Webots. The purpose is to use it as a simulator for the development of BHIR prototypes. Firstly, 3D boiler header pipe environment is constructed by using Pro Engineer (Pro\E). Next, Virtual Reality Modeling Language or VRML97 is used to convert file from Pro\E world file to Webots world file. Finally, simulations are carried out to verify the effectiveness of the developed 3Dboiler header environment template. Results show the advantages of having the simulator for modeling and designing of BHIR prototypes. 2012 The Authors.